Designing Magnetism in High Entropy Oxides (Adv. Sci. 10/2022). Issue 10 (5th April 2022) - Mazza, Alessandro R.; Skoropata, Elizabeth; Sharma, Yogesh; Lapano, Jason; Heitmann, Thomas W.; Musico, Brianna L.; Keppens, Veerle; Gai, Zheng; Freeland, John W.; Charlton, Timothy R.; Brahlek, Matthew; Moreo, Adriana; et al.
Abstract : High Entropy Oxides Manipulation of compositional disorder on a positionally ordered lattice in high entropy oxides demonstrates a possible route to designing quantum materials. Controlling the type and degree of the spin and exchange variance through composition allows continuous control over the magnetic phase—from macroscopically ordered states to frustration‐driven spin dynamics. More details can be found in article number 2200391 by Thomas Z. Ward and co‐workers.